2016
DOI: 10.1111/apm.12541
|View full text |Cite
|
Sign up to set email alerts
|

Syphilis epidemiology in 1994–2013, molecular epidemiological strain typing and determination of macrolide resistance in Treponema pallidum in 2013–2014 in Tuva Republic, Russia

Abstract: The incidence of syphilis in the Tuva Republic (geographical centre of Asia), Russia has been exceedingly high historically. No detailed examinations and no molecular investigations of Treponema pallidum strains transmitted in the Tuva Republic, or in general, in Russia, were published internationally. We examined the syphilis epidemiology in 1994-2013, and the molecular epidemiology and macrolide resistance in T. pallidum strains in 2013-2014 in the Tuva Republic. Among 95 mainly primary or secondary syphilis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0
7

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 35 publications
2
10
0
7
Order By: Relevance
“…1) (CAGGCGGCAGTGGCCACAGCCGCTGGAG GGTCCAGTGGTCGCAGCGATAATGGCAAC CACCCCGGCAAGGAACAGTTTCTCCAGTT) that was designated type "o". Most strains (31/ 47; 66%) belonged to subtype 14d/f, which is consistent with the findings of study in Tuva Republic, Russia (8).…”
supporting
confidence: 92%
“…1) (CAGGCGGCAGTGGCCACAGCCGCTGGAG GGTCCAGTGGTCGCAGCGATAATGGCAAC CACCCCGGCAAGGAACAGTTTCTCCAGTT) that was designated type "o". Most strains (31/ 47; 66%) belonged to subtype 14d/f, which is consistent with the findings of study in Tuva Republic, Russia (8).…”
supporting
confidence: 92%
“…In contrast to the MSM population, T. pallidum genotype diversity was limited in the heterosexual population in both males and females. The dominant genotype associated with female patients in our study was 14d/f, a genotype frequently identified around the globe, including in China (19,44,45), Peru (46), Russia (47), and the United States (19). It was assumed that certain T. pallidum subsp.…”
Section: Discussionmentioning
confidence: 78%
“…The first molecular epidemiological study of syphilis in EE was recently conducted, in the Tuva Republic, in southern Siberia: the authors estimated an incidence rate of 177 per 100,000 in 2013 and demonstrated that the 14d/f T.pallidum strain caused 91% of the syphilis cases [64]; this study also reported a 2.4% prevalence of macrolide-resistance (23S rRNA A2058G). A recent report from the Czech Republic has documented a substantial increase in macrolide-resistant strains (A2058G and A2059G 23S rRNA) over time [65,66], consistent with findings from elsewhere in Europe and globally [67].…”
Section: Syphilismentioning
confidence: 84%